Modulating P2X7 Receptor Signaling during Rheumatoid Arthritis: New Therapeutic Approaches for Bisphosphonates - Alberto Baroja-Mazo; Pablo Pelegrín (Journal of Osteoporosis)
P2X7 receptor-mediated purinergic signaling is a well-known mechanism involved in bone remodeling. The P2X7 receptor has been implicated in the pathophysiology of various bone and cartilage diseases, including rheumatoid arthritis (RA), a widespread and complex chronic inflammatory disorder. The P2X7 receptor induces the release into the synovial fluid of the proinflammatory factors (e.g., interleukin-1β, prostaglandins, and proteases) responsible for the clinical symptoms of RA. Thus, the P2X7 receptor is emerging as a novel anti-inflammatory therapeutic target, and various selective P2X7 receptor antagonists are under clinical trials. Extracellular ATP signaling acting through the P2X7 receptor is a complex and dynamic scenario, which varies over the course of inflammation. This signaling is partially modulated by the activity of ectonucleotidases, which degrade extracellular ATP to generate other active molecules such as adenosine or pyrophosphates. Recent evidence suggests differential extracellular metabolism of ATP during the resolution of inflammation to generate pyrophosphates. Extracellular pyrophosphate dampens proinflammatory signaling by promoting alternative macrophage activation. Our paper shows that bisphosphonates are metabolically stable pyrophosphate analogues that are able to mimic the anti-inflammatory function of pyrophosphates. Bisphosphonates are arising per se as promising anti-inflammatory drugs to treat RA, and this therapy could be improved when administrated in combination with P2X7 receptor antagonists.